2004
DOI: 10.1002/aheh.200300523
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Cyanobacteria in Greek Freshwaters, 1987—2000: Occurrence, Toxicity, and Impacts in the Mediterranean Region

Abstract: In a survey in Greece from 1987 to 2000 hepatotoxic cyanobacterial blooms were observed in 9 out of 33 freshwaters. Microcystins (MCYSTs) were detected by HPLC in 7 of these lakes, and the total MCYST concentration per scum dry weight ranged from 50.3 to 1638 ± 464 μg g—1. Cyanobacterial genera (Microcystis, Anabaena, Anabaenopsis, Aphanizomenon, Cylindrospermopsis) with known toxin producing taxa were present in 31 freshwaters. From our data and a review of the literature, it would appear that Mediterranean c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
2
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 63 publications
(73 reference statements)
7
55
2
3
Order By: Relevance
“…The data presented in this paper demonstrate that potentially toxic cyanobacteria were present in all the reservoirs studied throughout the entire sampling period, and that they became dominant at least once a year, especially from September to November. This period in which potentially toxic cyanobacteria were abundant in the phytoplankton community is similar to those in other Mediterranean countries, such as Greece, where potentially toxic cyanobacteria usually dominate from May to December (Cook et al, 2004;and references therein), and Israel, where potentially toxic cyanobacteria appear in Kinneret Lake in summer-autumn (Zohary, 2004).…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…The data presented in this paper demonstrate that potentially toxic cyanobacteria were present in all the reservoirs studied throughout the entire sampling period, and that they became dominant at least once a year, especially from September to November. This period in which potentially toxic cyanobacteria were abundant in the phytoplankton community is similar to those in other Mediterranean countries, such as Greece, where potentially toxic cyanobacteria usually dominate from May to December (Cook et al, 2004;and references therein), and Israel, where potentially toxic cyanobacteria appear in Kinneret Lake in summer-autumn (Zohary, 2004).…”
Section: Discussionsupporting
confidence: 63%
“…At this threshold value, five of the eight reservoirs analysed (62%) commonly showed blooms (those in this study and the Atazar reservoir; Almodovar et al, 2004;Barco et al, 2004). The prevalence of potentially toxic cyanobacterial blooms observed in this study is higher than the value found in other Mediterranean countries, such as Greece, where 27% of the waterbodies had blooms, of which 77.8% were toxic (Cook et al, 2004). This divergence could be partly explained by the fact that our study was based on high-frequency (weekly) sampling during the typical blooming period.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations